Prioritization of Industrial Symbiosis Enablers Using a Hesitant Fuzzy SWARA Approach - Sinan Çıkmak (İşletme Bilimi Dergisi)
Industrial symbiosis (IS), a crucial tool for reducing industrial waste, preventing pollution, and enhancing resource efficiency, is emerging as one of the sustainable approaches. IS is a network structure in which independent industrial enterprises cooperate and use the waste or by-products of one as raw material for the other. This synergistic network structure can help companies reduce costs, boost efficiency, and lessen negative environmental impacts. However, successful IS implementation relies on key enabling factors facilitating collaboration and ensuring mutual benefits among participants. This study focuses on Türkiye, where the development of IS networks holds significant potential due to its industrial diversity and growing emphasis on sustainability. It aims to rank the critical enabling factors in fostering these networks. To achieve this aim, Stepwise Weight Assessment Ratio Analysis (SWARA), a subjective multi-criteria decision-making (MCDM) technique that systematically evaluates and ranks criteria based on expert judgments, was employed. This approach was integrated with hesitant fuzzy sets to account for uncertainty and hesitation in expert opinions, ensuring a more robust assessment of the enabling factors. In the present study, a comprehensive literature review and expert opinions were employed to identify 23 sub-enablers falling under five main dimensions. The hesitant fuzzy SWARA method was then applied to calculate their importance weights. The results of the study indicate that the five most critical sub-enablers are, in descending order of importance: "reduction of raw material costs," "interest and support from top management," "reduction of waste disposal costs," "geographical proximity," and "openness to new business ideas."